Transformasi Ideologi Islam Berkemajuan dalam Masyarakat Islam Tradisional - Alvin Maulana; Sholihul Huda; Mukayat Al-Amin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the transformation of Progressive Islamic ideology promoted by Muhammadiyah within a traditional Muslim community in Waru Barat Village, Pamekasan, Madura. The socio-religious structure of the community, characterized by the dominance of Islamic boarding schools, the central authority of kiai, and deeply rooted cultural obedience, has shaped a gradual and often resistant response to reformist ideas. This research employs a qualitative field study approach. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive-interpretative methods within sociological and historical frameworks. The findings reveal that ideological transformation did not occur instantly but evolved through cultural negotiation and persuasive da’wah strategies. In its initial phase, the movement encountered ideological rigidity, religious exclusivism, and symbolic conflict. However, through strengthening educational institutions as Muhammadiyah’s charitable enterprises, Progressive Islamic values were gradually internalized. Education functioned as a strategic instrument in reducing ideological tensions and fostering a more rational, inclusive, and adaptive religious outlook without erasing local identity. This study highlights that ideological transformation in traditional societies requires dialogical, contextual, and long-term approaches